Bimbingan Teknis Kontrak Pinjaman/Pembiayaan dan Peningkatan Agunan bagi Manager Koperasi Kabupaten Bandung - Iwan Mulyana (E-Coops-Day, 2023)
Competency test technical guidance for cooperative managers held by the Bandung Regency KUKM Service from 23 to 25 August 2022 in collaboration with the Indonesian Cooperative University campus is an activity in preparing cooperative managers to be able to take competency tests according to skills required to become certified manager. Technical guidance carried out, especially by presenters related to Loan/Financing and Collateral Improvement Contracts. The method given in this Bimtek is to provide two-way material and discussion regarding problems that arise in loan/financing contracts and binding guarantees by providing solutions needed by Bimtek participants. The topics given to cooperative managers will provide a deeper understanding of good loan contract execution. This Bimtek activity will be used as internal reinforcement for cooperative managers in facing the competency test that will be followed.